Donor-Derived CD7 CAR-T Therapy Followed by Allogeneic Hematopoietic Stem Cell Transplantation for Acute T-Lymphocytic Leukemia Associated With Hepatitis B: A Case Report - Li, Zhihui; Meng, Fanqiao; Li, Jing; Wu, Tong (Frontiers in Immunology, 2022)
The use of chimeric antigen receptor T cells (CAR-Ts) is effective in the treatment of hematological malignancies. It has been reported that HBV is reactivated after CAR-T immunotherapy for refractory/relapsed hematological malignant B-cell tumors. However, there is little literature on donor-derived CAR-T therapy combined with allogeneic hematopoietic stem cell transplantation in hepatitis B patients with acute T-lymphocytic leukemia. We report the case of one patient with hepatitis B associated with relapsed/refractory acute T-lymphocytic leukemia (T-ALL) treated with donor-derived CD7 CAR-T therapy and allogeneic hematopoietic stem cell transplantation. During treatment, the copy number of hepatitis B virus continuously decreased, and AST, ALT, DBIL and TBIL remained within the controllable range. CD7-negative MRD levels recurred 4.5 months after transplantation, and the flow cytometry results became negative after immunosuppressive reduction. Seven months after transplantation, the patient had complete remission, and the copy number of hepatitis B virus decreased to below 102.This is the first study on the safety and effectiveness of donor-derived CD7 CAR-T therapy bridging allogeneic hematopoietic stem cell transplantation in a patient with relapsed/refractory acute T-lymphocytic leukemia and hepatitis B.